The method of long-term catheterization of the vena jugularis in pigs - Klein, Pavel; Nalos, Lukas; Dejmek, Jiri; Soukup, Martin (Journal of pharmacological and toxicological methods, 2019)
INTRODUCTION: The pig is one of the most valuable in vivo models in biomedical research, however with only a few well-accessible veins suitable for venipuncture. Moreover, most of the known methods of blood collection are suitable only for a limited time period. The aim of the study was to verify an improved method of long-term catheterization of the jugular vein in pigs. METHODS: A 420 mm polyurethane catheter 16G tube was surgically inserted using the Seldinger technique. The part of the tube that was not inserted into the vein was threaded through a subcutaneously introduced trocar into the occipital area, where it was well accessible and well protected from damage. The catheters were flushed with sterile 0.9% saline solution and locked with 4% citrate between frequent blood samplings, or with 30% citrate at intervals of 1-2-days. Once a week, the catheters were locked with 4% citrate containing taurolidine for 24 h in order to prevent infection. The method was verified in 14 pigs. RESULTS: The catheters were fully functional for up to 11 weeks and no infection or thrombus was observed. DISCUSSION: This method of catheterization and catheter care allows the realization of long-term experiments with comfortable and stress-free blood sampling.
Keywords: Blood Specimen Collection; zvířata; Male; Female; Thiadiazines; Jugular vein; thiadiaziny; katetrizace; venae jugulares; Jugular Veins; Catheterization; Pig; Permanent intravenous catheterization; Swine; Animals; Taurine; mužské pohlaví; odběr vzorku krve; ženské pohlaví; prasata; taurin